Dual approach for internal fixation of a complex talar fracture in a 20-year-old male - Narkhede, Yogesh D. (International Journal of Research in Orthopaedics, 2025)
Talus bone plays a pivotal role in foot and ankle function. Due to its inherent blood supply, talar fracture poses high risk of AVN (avascular necrosis). The objective of this case report was to provide valuable insights into the surgical management of this unique talar fracture, shedding light on the efficacy of specific surgical techniques and the absence of avascular necrosis in the patient's 18-month postoperative follow-up. By detailing the distinct characteristics and management of this complex talar fracture, we hope to contribute to the existing body of knowledge on talus fractures and aid in the development of improved treatment approaches for similar cases. A 20-year-old male with a history of fall, presented to hospital after 1 day of fall with swelling, tenderness around foot and ankle, ecchymosis. the patient was evaluated in the form of imaging and blood work up and planned for surgery. open reduction and internal fixation were done with Herbert screws. talus was approached through anteromedial and anterolateral incisions without medial malleolus osteotomy. Identification of fracture patterns is crucial for management and outcome. Dual incision facilitates disimpaction, accessing talar dome area. At 18 months the outcome was satisfactory painless ROM, with no signs of AVN.